PULL AND BENDING FORCE CARBON FIBER COMPOSITE - Moh Ardi Cahyono; Laura Laksamana (Institut Teknologi Dirgantara Adisutjipto, 2020)
Based on the test data, it can be seen that the average stress value on the carbon fiber composite with the fiber direction of 0 ° -30 ° -60 ° has the highest tensile stress value in the TA 2 specimen, namely 121.439 MPa, the highest strain value in the TA 1 specimen is 0.031, the value The highest modulus of elasticity in the TA 3 specimen is 438,460 MPa, while for the fiber direction 0 ° -45 ° -90 ° the highest tensile stress value in the TB 3 specimen is 670.691 MPa, the highest strain value in the TB 3 specimen is 0.096, the highest elasticity modulus value in the specimen TB1 is 1076,993 MPa.